LAW ENFORCEMENT EFFORTS AGAINST LIMESTONE MINING ACTIVITIES IN TAMANSARI VILLAGE, PANGKALAN DISTRICT ARE LINKED TO LAW NUMBER 3 OF 2020 CONCERNING AMENDMENTS TO LAW NUMBER 4 OF 2009 CONCERNING MINERAL AND COAL MINING - Setiawathi, Maya; Hidayat, Anwar; Arafat, Zarisnov (Justisi: Jurnal Ilmu Hukum, 2024)
Law enforcement is the process of making efforts to uphold or function legal norms in real terms as a behavioral guideline in the legal relationship of community life. Mining crimes are acts that are prohibited by regulations that are subject to sanctions for perpetrators, in order to protect mineral and coal mining activities and businesses. Mining actors who do not have a permit are regulated in Article 158 of Law Number 3 of 2020 concerning Amendments to Law Number 4 of 2009 concerning Mineral and Coal Mining. This action in limestone mining causes environmental damage and also triggers various negative impacts. The results of this study discuss how law enforcement efforts carried out by the Pangkalan Police in overcoming mining that does not have a permit in Tamansari Village, Pangkalan District and discuss the impact of the cause of air pollution in Tamansari Village, Pangkalan District as a result of this limestone mining. The empirical juridical research method used to answer the problems in this study with primary data sources consisting of the surrounding community, mining workers, community leaders, and law enforcement officials such as the police. The conclusion that can be drawn is that law enforcement efforts have not been maximized in overcoming mining that does not have permits because of the many resistance from the community, so further efforts are needed so that the public is aware of the law in Indonesia.